NILAI TAMBAH DAN KEUNTUNGAN USAHA PUPUK ORGANIK MAJU JAYA DI DESA ALEBO KECAMATAN KONDA KABUPATEN KONAWE SELATAN - Dedu, La Ode Arfan; Batoa, Hartina; Alwi, La Ode; Gafaruddin, Abdul; Sudarmo, Hadi; Arif, La Ode Kasno; Jabuddin, La Ode (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
Cow manure converted into organic fertiliser is of good quality and has a high sales value. The use of faeces and urine as organic fertiliser is very beneficial, especially for soil fertility, and provides the necessary nutrients for plants. The village of Alebo has a majority of farmers, so fertilizer is the main need for the management of crops such as rice, maize, sweet potato, beans and other crops, as well as in the surrounding village communities, which also have a majority of rice fields and are farmers. Urban communities also need fertilizers to fertilize ornamental plants in their gardens. The processing of cow dung into organic fertiliser in Alebo village, Konda sub-district, is one of the areas affected by the covid-19 virus pandemic, so it is important to analyse the added value and benefits of organic fertiliser production. The objective of this study is to analyze the added value and benefits of organic fertilizer manufacturing activities after the covid-19 pandemic in Alebo village, Konda sub-county. This study should serve as a demonstration tool for other districts or surrounding villages that have not yet converted cow dung into organic fertilizer, as well as a training forum for farmers/ranchers in agricultural areas to integrate agriculture and livestock production in synergy in the same area to support the realization of food self-sufficiency. The results showed that value added and profits generally declined before the covid-19 programme and that while the covid-19 programme actually led to a decline in activity, the post-covid-19